pvl-carried methicillin resistant Staphylococcus aureus isolated from hospitalized patients in Baghdad, Iraq: none - Ibraheem, Hind Tahseen; Al-Mathkhury, Harith Jabbar Fahad (Iraqi Journal of Science, 2018)
Out of 150 different specimens, 67 S. aureus isolate were isolated. However, 16sRNA gene was located only in 60 isolates. Moreover, mecA gene was located in 48 isolates; thereby MRSA covered 80% of all S. aureus isolates. Of considerable interest, pvl gene was detected in only six isolates (10%). Hence, the present work emphasizes the notion suggested that pvl is not an indicative of CA-MRSA.